Tumor Targeting Effect of Triphenylphosphonium Cations and Folic Acid Coated with Zr-89-Labeled Silica Nanoparticles - Gun Gyun Kim; Jun Young Lee; Pyeong Seok Choi; Sang Wook Kim; Jeong Hoon Park (Molecules, 2020)
In this study, we investigated the tumor targeting effect in cancer cells using triphenylphosphonium (TPP) cations, which are accumulated by differences in membrane potential, and folic acid (FA), which is selectively bound to overexpressed receptors on various cancer cells. We used Food and Drug Administration (FDA)-approved silica nanoparticles (SNPs) as drug carriers, and SNPs conjugated with TPP and FA (STFs) samples were prepared by introducing different amounts of TPP and FA onto the nanoparticle surfaces. STF-1, 2, 3, 4 and 5 are named according to the combination ratio of TPP and FA on the particle surface. To confirm the tumor targeting effect, 89Zr (t1/2 = 3.3 days) was coordinated directly to the silanol group of SNP surfaces without chelators. It was shown that the radiochemical yield was 69% and radiochemical purity was >99%. In the cellular uptake evaluation, SNPs with the most TPP (SFT-5) and FA (SFT-1) attached indicated similar uptake tendencies for mouse colon cancer cells (CT-26). However, the results of the cell internalization assay and measurement of positron emission tomography (PET) images showed that SFT-5 had more affinity for the CT-26 tumor than other samples the TPP ratio of which was lower. Consequently, we confirmed that TPP ligands affect target cancer cells more than FA, which means that cell membrane potential is significantly effective for tumor targeting.